What Lane? - Maldonado, Torrey (New York : Nancy Paulsen Books, 2020)
Biracial sixth-grader Stephen questions the limitations society puts on him after he notices the way strangers treat him when he hangs out with his white friends and learns about the Black Lives Matter movement.
Keywords: Racism -- Juvenile fiction; Friendship -- Juvenile fiction; Black Lives Matter movement -- Juvenile fiction; Racially mixed people -- Juvenile fiction; African Americans -- Juvenile fiction; Brooklyn (New York, N.Y.) -- Juvenile fiction; Racism -- Fiction; Friendship -- Fiction; Black Lives Matter movement -- Fiction; Racially mixed people -- Fiction; African Americans -- Fiction; Brooklyn (New York, N.Y.) -- Fiction